Talent management challenges in the Gambian public sector: A qualitative literature-based analysis - Lamin Saidyjeng (Privietlab, 2026)
Talent management is a strategic human resource management (HRM) practice essential for attracting, developing, and retaining skilled employees. In the public sector of developing countries, systemic constraints often undermine effective talent management. This study examines talent management challenges in the Gambian public sector through a qualitative literature‑based analysis. Drawing on peer‑reviewed articles, government policy documents, civil service regulations, and institutional reports, the study employs thematic analysis to identify constraints across the talent management cycle. The findings reveal weak strategic workforce planning, rigid recruitment and promotion systems, inadequate training and development, poor succession planning, chronic retention problems, and institutional and political constraints. A multi‑level typology institutional, organizational, and individual is proposed to structure these challenges. The study is informed by the Resource‑Based View, Institutional Theory, and Public Service Motivation, which together explain how human capital underutilization, regulatory rigidity, and motivational limits interact to shape talent management outcomes. The study contributes a theory‑informed synthesis of talent management constraints and offers policy implications for HRM reforms in the Gambian public sector, including increasing managerial autonomy, strengthening merit‑based practices, and investing in leadership development.